Mapping of High-Spatial-Resolution Three-Dimensional Electron Density by Combing of Full-Polarimetric SAR and IRI Model - Zhu, Wu; Chen, Jing-Yuan; Zhang, Qin; Zhang, Jin-Min (Frontiers in Earth Science, 2020)
Retrieval of ionospheric parameters from spaceborne synthetic aperture radar (SAR) and SAR interferometry observations has been developed in recent years because of its high spatial resolution. However, current studies are centered on the one-dimensional or two-dimensional ionospheric parameters, and there is a lack of retrieving three-dimensional ionospheric electron density. Based on this background, this study proposes an efficient method to map high-spatial-resolution three-dimensional electron density by combing of the full-polarimetric SAR images and International Reference Ionosphere (IRI) model. For a performance test of the proposed method, two L-band Advanced Land Observation Satellite Phase Array L-band SAR full-polarimetric SAR images over Alaska regions are processed. The high-spatial-resolution ionospheric parameters, including vertical total electron content and three-dimensional ionospheric electron density, are reconstructed over the study area. When comparing with the electron density derived from Poker Flat Incoherent Scatter Radar (PFISR) system, it is found that the IRI-derived electron density is obviously improved, where the standard deviations of differences between PFISR and IRI decrease, respectively, by 2 and 1.5 times compared to those before the correction, demonstrating the reliability of the proposed method. This study can help us better understand the characteristics of ionospheric variation in space.